2020
DOI: 10.1080/14772000.2020.1769224
|View full text |Cite
|
Sign up to set email alerts
|

The Type Locality Project: collecting genomic-quality, topotypic vouchers and training the next generation of specimen-based researchers

Abstract: DNA evidence is often critical for taxonomic studies; however, many historical type specimens lack corresponding genetic samples, which limits contemporary molecular research questions and may restrict conservation and management decisions. We conducted a pilot Type Locality Project to collect voucher specimens and genomic-grade samples from amphibian type localities in the state of Virginia, USA. These samples can serve as proxies for cases in which obtaining genomic data from the type specimen is not possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…This has also prevented the accurate naming of some Antirrhinum populations. In contrast, our study offers a new phylogenetic hypothesis that helps to elucidate systematics and evolution thanks to a high number of phylogenetically informative nucleotide characters (>50,000 bp) taken from genome-wide (GBS) sequences, together with DNA sequences that are anchored to original Antirrhinum names (Bell et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has also prevented the accurate naming of some Antirrhinum populations. In contrast, our study offers a new phylogenetic hypothesis that helps to elucidate systematics and evolution thanks to a high number of phylogenetically informative nucleotide characters (>50,000 bp) taken from genome-wide (GBS) sequences, together with DNA sequences that are anchored to original Antirrhinum names (Bell et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis of an evolutionary radiation of Antirrhinum based on ITS and plastid sequences (Vargas et al, 2009) is supported by our phylogenetic analysis based on GBS data, which found a high rate of diversification (0.54 spp. Myr −1 ) into at least 26 species (Valente et al, 2010;Bell et al, 2012) since the Pliocene (Vargas et al, 2009). The combination of terrain complexity and eco-climatic novelty seems to explain why the Mediterranean basin contains numerous examples of explosive radiations in the angiosperms (Valente et al, 2010).…”
Section: Radiation and Geographical Speciation Of Antirrhinummentioning
confidence: 99%
“…Several other sequences from that study [41] appear to have resulted from PCR contamination: one identified in BOLD and GenBank as a skink (Plestiodon) is a 97% match to a copepod, and several others identified as three distantly related lizard species are 98-99% identical to sequences from one salamander species. Many of the amphibian sequences in that study were also associated with mis-identified specimens or outdated taxonomies (see Bell et al [68]). The lesson here is that all specimen identifications should be checked before publishing, making sure that the vouchers are identified correctly and the taxonomy is up to date.…”
Section: Specimen Identificationmentioning
confidence: 97%
“…Through mutual sharing of best practices in a virtual community of practice, biorepository personnel can standardize and prioritize the types of materials and preservations most useful to EID research. Likewise, the EID community can better integrate biorepository data standards into specimen collection and sampling procedures [5,21,[76][77][78]. Darwin Core (dwc.…”
Section: Project Echo: a Global Communication Network To Unite Biorepositories And Biomedicinementioning
confidence: 99%
“…Through mutual sharing of best practices in a virtual community of practice, biorepository personnel can standardize and prioritize the types of materials and preservations most useful to EID research. Likewise, the EID community can better integrate biorepository data standards into specimen collection and sampling procedures [ 5 , 21 , 76 78 ]. Darwin Core ( dwc.tdwg.org ) stable identifiers, for example, represent a common vocabulary intended to facilitate the sharing of information about biological diversity and specimens [ 79 ].…”
Section: Introductionmentioning
confidence: 99%